Lectures on Land Warfare; A tactical Manual for the Use of Infantry Officers : An Examination of the Principles Which Underlie the Art of Warfare, with Illustrations of the Principles by Examples Taken from Military History, from the Battle of Thermopylae, B.C. 480, to the Battle of the Sambre, November 1-11, 1918 - Anonymous (Salt Lake City, UT : Project Gutenberg, 2007)
"Lectures on Land Warfare; A Tactical Manual for the Use of Infantry Officers" is a military manual written in the early 20th century. This work serves as a comprehensive examination of the principles underlying warfare, focusing specifically on the tactical application of these principles for infantry officers, while drawing on various historical military examples. The beginning of this manual sets the stage for a detailed exploration of military tactics and strategies, emphasizing the importance of understanding fixed principles in warfare. In the opening chapters, the author critiques popular misconceptions about warfare, such as the belief that it can solely rely on common sense or that strategic thinking is exclusive to higher-ranking officers. Detailed discussions introduce key concepts like the significance of moral force, the interplay between strategy and tactics, and the necessity for extensive study of military history to inform proper decision-making in the face of conflict. The manual aims to fortify infantry officers with knowledge that will shape their effectiveness in battle, with references spanning historical contexts from classical warfare to World War I. (This is an automatically generated summary.)
Release date is 2007-11-14
E-text prepared by Al Haines
Keywords: Military art and science; Tactics